Embryonic and foetal expression patterns of the ciliopathy gene CEP164. - L A Devlin; S A Ramsbottom; L M Overman; S N Lisgo; G Clowry; E Molinari; L Powell; C G Miles; J A Sayer (PLoS ONE, 2020)
Nephronophthisis-related ciliopathies (NPHP-RC) are a group of inherited genetic disorders that share a defect in the formation, maintenance or functioning of the primary cilium complex, causing progressive cystic kidney disease and other clinical manifestations. Mutations in centrosomal protein 164 kDa (CEP164), also known as NPHP15, have been identified as a cause of NPHP-RC. Here we have utilised the MRC-Wellcome Trust Human Developmental Biology Resource (HDBR) to perform immunohistochemistry studies on human embryonic and foetal tissues to determine the expression patterns of CEP164 during development. Notably expression is widespread, yet defined, in multiple organs including the kidney, retina and cerebellum. Murine studies demonstrated an almost identical Cep164 expression pattern. Taken together, these data support a conserved role for CEP164 throughout the development of numerous organs, which, we suggest, accounts for the multi-system disease phenotype of CEP164-mediated NPHP-RC.